ANALISIS PRIORITAS PEMBANGUNAN WILAYAH BERDASARKAN SEKTOR PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN TAPANULI TENGAH-SUMATERA UTARA - Rita Herawaty Bangun (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2018)
Abstract. This study aims to analyze the growth classification of the economic sector, analyze the shifts in the economic sector and identify the leading sectors in the District of Tapanuli Tengah, Province of Sumatera Utara for the determination of regional development priorities. The analytical tool used in this research were klassen typology (KT) analysis, loqation question (LQ) analysis and shift share (SS) analysis. The calculation of KT analysis show that the district of Tapanuli tengah was included the regional having potential for develop and growth economically in province of Sumatera Utara. the The results of the calculation of the LQ analysis show that sector of the agriculture, forestry and fisheries; electricity and gas procurement; water supply; waste management; waste and recycling and government administration, defense and compulsory social security; were the leading sectors in Tapanuli Tengah. Furthermore, the results of the SS analysis show the sector of mining and quarrying; electricity and gas procurement; water supply; waste management, waste and recycling; construction; wholesale and retail trade in car and motorcycle repair; transportation and warehousing; provision of accommodation and drinking; financial services and insurance; government administration, defense and social security must have high competitiveness and have the potential to progress and grow that can increase the economic growth of Tapanuli Tengah.